2008
DOI: 10.1063/1.2830008
|View full text |Cite
|
Sign up to set email alerts
|

Exchange-biased planar Hall effect sensor optimized for biosensor applications

Abstract: This article presents experimental investigations of exchange-biased Permalloy planar Hall effect sensor crosses with a fixed active area of w ϫ w =40ϫ 40 m 2 and Permalloy thicknesses of t = 20, 30, and 50 nm. It is shown that a single domain model describes the system well and that the thicker film will have a higher signal as well as a lower noise. It is estimated that the signal-to-noise ratio for bead detection increases by a factor 2.1 when t is increased from 20 to 50 nm and hence a higher t is benefici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 9 publications
0
29
0
Order By: Relevance
“…32 However, in our previous studies, no significant indications of such a relaxation were observed for permalloy thicknesses up to 50 nm. 33 The edge relaxation becomes more energetically favorable when the exchangepinning is weakened, and therefore, the effective single domain shape anisotropy B sh is reduced. The combined effect of the shape anisotropy and reduction of B ex for the investigated sensor geometry and stack compositions was that no gain inS 0 could be obtained by increasing t FM above 20 nm (Fig.…”
Section: A Effects Of T Cu and T Fm On Sensor Behaviormentioning
confidence: 99%
“…32 However, in our previous studies, no significant indications of such a relaxation were observed for permalloy thicknesses up to 50 nm. 33 The edge relaxation becomes more energetically favorable when the exchangepinning is weakened, and therefore, the effective single domain shape anisotropy B sh is reduced. The combined effect of the shape anisotropy and reduction of B ex for the investigated sensor geometry and stack compositions was that no gain inS 0 could be obtained by increasing t FM above 20 nm (Fig.…”
Section: A Effects Of T Cu and T Fm On Sensor Behaviormentioning
confidence: 99%
“…1. For low fields along the -direction, the sensor output is (1) where is the sensor sensitivity [10]. The sensitivity for the sensors used in the experiments was found to V m/A .…”
Section: A System Design and Fabricationmentioning
confidence: 99%
“…Consequently, the knee frequency is independent of the PHEB geometry, since D B has the same dependence on nlwt FM in both frequency regimes. Increasing t FM is the most effective measure to reduce D B , however, t FM can only be increased as long as the single-domain configuration is maintained -the limit being around 50 nm [25]. On the other hand, nlw can be increased several orders of magnitude without loosing the single-domain configuration.…”
Section: Figure 4 Herementioning
confidence: 99%